2012
DOI: 10.1016/j.jcv.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 mother-to-child transmission and drug resistance among Brazilian pregnant women with high access to diagnosis and prophylactic measures

Abstract: In this study delayed disclosure of diagnosis, partial/no preventive measures, drug resistance among asymptomatic women under prophylaxis and MTCT in low viremic mothers raise concerns. The expansion of subtype C infection corroborates surveillance of HIV-1 diversity in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…A previous regional study investigating different subpopulations reported a low rate of subtype C among infected patients [58]. However, recent molecular epidemiology studies have shown a significant increase in rates of HIV-1 subtype C among pregnant women living in small interior cities in central western Brazil [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous regional study investigating different subpopulations reported a low rate of subtype C among infected patients [58]. However, recent molecular epidemiology studies have shown a significant increase in rates of HIV-1 subtype C among pregnant women living in small interior cities in central western Brazil [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Among pregnant women, recent molecular data from central Brazil have shown an unexpectedly high prevalence of subtype C viruses, which are strongly related to those circulating in southern/southeastern Brazil [13]. …”
Section: Introductionmentioning
confidence: 99%
“…New PR/RT subtype C sequences were obtained from 32 individuals from RJ selected from a larger cohort of about 3,000 HIV-infected patients followed at outpatient clinics from the Public Health System distributed throughout the state that underwent HIV genotyping tests at the Laboratory of AIDS and Molecular Immunology (FIOCRUZ) between 2002 and 2011, as previously described [20]. The HIV-1 subtype C pol sequences from RJ were combined with sequences from SP ( n = 18), GO ( n = 16), MT ( n = 4) and MS ( n = 4) available at the Los Álamos HIV Sequence Database ( www.hiv.lanl.gov ) and described elsewhere [10,14,15,16,17,18,21,22,23,24], and with a dataset of sequences isolated in the south region (RS = 55, SC = 41 and PR = 39) described in detail in a previous study [25]. The study was approved by the Instituto Oswaldo Cruz - Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The estimated vertical transmission rate was 6.8% in 2004, with a range from 13.4% in the North region to 4.3% in the Midwest region [10]. Local studies conducted in the Southeast region [11-14] have reported vertical transmission rates closer to 3%, while rates of less than or equal to 2% have been found in the Midwest and South regions [15-17]. In contrast, in the North and Northeast regions and in the state of São Paulo, local studies have found vertical transmission rates of 9.9% [18], 9.2% [19] and 6.0% [20], respectively.…”
Section: Introductionmentioning
confidence: 99%